Expression analysis of nuclear factor kappa B (NF-κB) in oral squamous cell carcinoma - Dev Arora; Dhanraj M. Ganapathy; Ashikha Shirin Usman Pp; K.P. Ameya; Durairaj Sekar; Kumaravel Kaliaperumal (Oral Oncology Reports)
Introduction: Oral squamous cell carcinoma (OSCC) is the most common cancer in the head and neck region. More than 45 % of the cancer cases in India are diagnosed as squamous cell carcinoma. Although much progress has been made in controlling OSCC in recent years, the management or treatment option for OSCC remains challenging. Interestingly, nuclear factor kappa B (NF-κB) is a protein complex that controls transcription of DNA, cytokine production, and cell survival. Thus, this study aims to evaluate the levels of NF-κB in OSCC patients and their adjacent normal tissue. Materials and method: A total of 20 OSCC and adjacent normal tissues were collected from the biopsy samples of Department of Oral and Maxillofacial Surgery, Saveetha Dental College, and Hospitals. The tissues were processed for Hematoxylin and Eosin staining and NF-κB gene expression studies. The data were shown as mean ± standard deviation and p<0.05* was statistically significant. Results and conclusion: Our histological observation findings showed that there was epithelial cell injury in the OSCC samples, which contributed to the creation of more keratin pearls. Additionally, our findings showed that as compared to normal tissue, OSCC samples had considerably greater NF-kB expression levels. As a result, we conclude that NF-κB was found to be an important oncogene in the tumor growth and metastasis of various cancers, including OSCC. Thus, inhibition of NF-κB can be postulated to be a potential treatment against OSCC.